MECHANISMS OF THE VERBALIZATION OF GENDER STEREOTYPES THROUGH LINGUISTIC UNITS IN LITERARY DISCOURSE - Rakhmanova Makhfuza Saparaliyevna (Bright Mind Publishing, 2026)
This article examines the mechanisms of the verbalization of gender stereotypes through linguistic units in literary discourse. The study analyzes how gender stereotypes are represented and reinforced in literary texts by means of lexical, phraseological, and syntactic devices. Particular attention is paid to the ways in which male and female characters are constructed through language and how socially and culturally shaped gender roles are reflected in discourse. Using a discourse-analytical approach, the research reveals the pragmatic and semantic features of evaluative linguistic units that contribute to the formation of gendered meanings. The findings of the study highlight the significant role of literary discourse in shaping readers’ perceptions of gender and demonstrate the theoretical and practical relevance of gender linguistics in the analysis of literary texts.
Keywords: Literary discourse, gender stereotypes, linguistic units, verbalization mechanisms, gender linguistics, discourse analysis, lexical and phraseological devices, pragmatics, semantics.